Long‐Acting Lipoglycopeptides Can Interfere With Vancomycin Therapeutic Drug Monitoring. (19th October 2021) - Smelter, Dan F.; Trisler, Michael J.; McCreary, Erin K.; Baker, Matthew; Copeland, Kenneth; Dilworth, Thomas J.; Rose, Warren E.
Abstract: Oritavancin and dalbavancin are long‐acting lipoglycopeptides with activity against susceptible gram‐positive bacteria, including methicillin‐resistant Staphylococcus aureus . Though similar in structure to traditional glycopeptide antibiotics like vancomycin, these antibiotics have terminal half‐lives >10 days, and, as a result, there is potential for administration of vancomycin to a patient while oritavancin or dalbavancin are still appreciably present in serum. Given the structural similarities, this creates an opportunity for lab assay interference when performing therapeutic drug monitoring for vancomycin. Following higher‐than‐expected serum vancomycin concentrations in a patient who received both oritavancin and vancomycin within a short time frame, we evaluated the potential for lipoglycopeptide interference with clinical vancomycin assays. Five platforms covering 3 immunoassay technologies were used to quantify vancomycin concentrations in serum spiked with oritavancin or dalbavancin. Oritavancin generated spurious vancomycin concentrations (20%‐84% increase) in both enzyme‐multiplied immunoassay technique and a particle‐enhanced turbidimetric inhibition immunoassay. However, the improper detection of oritavancin was not consistent across all particle‐enhanced turbidimetric inhibition immunoassay platforms. Dalbavancin interference was not detected on any of the platforms tested. The interference from oritavancin may result in falsely elevated vancomycin concentrations and, subsequently, inappropriately adjusted vancomycin doses.